Effects of Different Crosslinkers on the Release Profiles of Growth Factors (TGF-ß, BMP and PDGF) From Hydroxyapatite Combined With Secretomes - Purnamasari, Yunita; Mahyudin, Ferdiansyah; Edward, Mouli (Scripta Medica, 2026)
Background/Aim: Controlled release of growth factors is essential for bone regeneration, requiring biomaterials with high stability and osteoconductivity. Hydroxyapatite (HA) is biocompatible and osteoconductive but limited by weak mechanical strength and uncontrolled growth factor release. This study evaluated the release profiles of transforming growth factor-beta (TGF-β), bone morphogenetic protein (BMP) and platelet-derived growth factor (PDGF) from HA combined with secretome and crosslinked using polyvinyl alcohol (PVA), glutaraldehyde (GA), or aluminium hydroxide gel (Alhydrogel), aiming to identify the most effective crosslinker for controlled release and scaffold stability. Methods: In vitro tests were conducted on four groups (n = 6 each): HA + PVA 0.5 % + Secretome, HA + GA 0.1 % + Secretome, HA + Alhydrogel 0.1 % + Secretome and a non-crosslinked control. HA derived from bovine bone was sterilised using gamma radiation, then crosslinked through immersion and dry-heat treatment. Samples were incubated in PBS at 37 °C and growth factor release was analysed using ELISA on days 1, 3, 7, 10 and 14. Results: HA + PVA showed the highest TGF-β release (617.90 ± 18.66 ng/L) and the most stable BMP (0.19 ng/L) and PDGF (0.61 ng/L) profiles. HA + Alhydrogel had the highest BMP release (6.01 ± 0.50 ng/L) and stable TGF-β (7.57 ng/L), while HA + GA had the highest PDGF release (27.27 ± 1.92 ng/L). The control showed rapid but unstable release. Conclusion: HA combined with secretome and PVA offers the most stable and sustained release, supporting its use as an optimal scaffold for bone regeneration.